Seasonal variations in groundwater upwelling zones in a Danish lowland stream analyzed using Distributed Temperature Sensing (DTS). Issue 3 (14th January 2013) - Matheswaran, Karthikeyan; Blemmer, Morten; Rosbjerg, Dan; Boegh, Eva
Abstract The distribution of groundwater inflows in a stream reach plays a major role in controlling the stream temperature, a vital component shaping the riverine ecosystem. In this study, the Distributed Temperature Sensing (DTS) system was installed in a small Danish lowland stream, Elverdamsåen, to assess the seasonal dynamics of groundwater inflow zones using high spatial (1 m) and temporal (3 minutes) resolution of water temperature measurements. Four simple criteria consisting of 30 min average temperature at 16:00, mean and standard deviation of diurnal temperatures, and the day–night temperature difference were applied to three DTS datasets representing stream temperature responses to the variable meteorological and hydrological conditions prevailing in summer, winter and spring. The standard deviation criterion was useful to identify groundwater discharge zones in summer and spring conditions, while the mean temperature criterion was better for the winter conditions. In total, 20 interactions were identified from the DTS datasets representing summer, 16 in winter and 19 in spring, albeit with only two interactions contributing in all three seasons. Higher baseflow to streamflow ratio, antecedent precipitation and presence of fractured clayey till in the stream reach were deemed as the vital factors causing apparent seasonal variation in the locations of upwelling zones, prompting use of DTS not only in preconceived scenarios of large diurnal temperature change but rather a long‐term deployment covering variable meteorological and hydrological scenarios. Copyright © 2012 John Wiley & Sons, Ltd.